Review Artikel: Hubungan Status Gizi dengan Malaria pada Balita - Lhidya Halizah Malik; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Malaria is an infection caused by parasites of the genus Plasmodium. Malnutrition is a complex phenomenon because its aetiology is multifactorial, and its clinical manifestations vary; acute malnutrition manifests as underweight, while chronic malnutrition manifests as stunting. Nutritional status is related to the immune response to infection. On the one hand, nutritional status is also essential in the risk and prognosis of infectious diseases, such as malaria. The complex relationship between malaria and malnutrition, the personal impact of these diseases and their combination on children under five is enormous. The aim was to determine the relationship between nutritional status and malaria incidence in children under five. It is also hoped that the explanation from this review will make the public pay attention to health in compiling this review, using the literature study method in the form of primary references in the form of national and international journals for the last ten years. Then, in compiling this review using online media, namely Google Scholar. From the results of this difference in results, it may be caused by several factors, such as parental occupation, immunity, parental knowledge, and place of residence.